Configuración de las estrategias de afrontamiento de las mujeres con diagnóstico de cáncer de mama de la Fundación Mujeres por tus Senos de la ciudad de Cartagena. (2023)
The present research performs an analysis and proposes an intervention program from the psychological coping strategies for breast cancer, used in the foundation Mujeres por tus Senos of the city of Cartagena, for the positive contribution in the lifestyle of women diagnosed with this disease. For this purpose, a qualitative approach was adopted, with an exploratory, narrative design, phenomenological criteria and descriptive scope. The focus group technique was used as an instrument to obtain key information on the coping process. The collection of information was deployed with the general director, and 7 women belonging to the foundation; the maximum number of points of view was collected from each of their experiences and experiences, both from those who generate the basic guidelines of care, as well as from those who have received the diagnosis. Once the instrument was implemented and the information was collected, an psychoeducational booklet was made, which is available at the foundation’s facilities, physically and with free access.